Air assist atomization characterization of palm biodiesel through experimental investigation and CFD simulation. Issue 5 (3rd September 2017) - Tan, Ee Sann; Anwar, M.; Kumaran, P.; Indra, T. M.; Yoshikawa, Kunio
ABSTRACT: The depletion of fossil fuel and environmental concerns have elevated biodiesel to emerge as a suitable alternative fuel to substitute diesel fuel. The study of spray formation is essential to improve the combustion systems of internal combustion engines and gas turbines. This paper aims to study the atomization characteristics of biodiesel derived from palm biodiesel through experimental test and simulation. The chemical fuel properties of biodiesel such as viscosity and density, will adversely affect the spray characteristics such as spray pattern, spray length, spray angle and Sauter Mean Diameter. The biodiesel fuels are blended with diesel in various ratios before being tested in an atomization test rig. Modelling of the atomizer are presented using computational fluid dynamics whereby comparisons are made with respect to the experimental results carried out in the atomizer test rig. There is no large discrepancy with the simulation results. The results showed that the higher content of biodiesel gives a larger droplet size and longer spray length. However, it produces smaller spray angle and spray width but with clearer vortex shape of spray pattern.